Zweiter Beitrag zur Kenntnis der Epermeniiden-Fauna Australiens und Ozeaniens (Lepidoptera). - Gaedike, Reinhard (Contributions to Entomology = Beiträge zur Entomologie, 1972)
This is the second contribution to our knowledge of the Epermeniidae of Australia and Ozeania. The revision led to the description of two new species (Ochromolopis paropsias, O. pseudaphronesa), and a new synonym could be estabished. The examination of the previously unknown male of Epermenia symmorias enabled us to finally decide to which genus this species belongs. Nomenclatural Actsparopsias Gaedike, 1972 (Ochromolopis), spec. n.pseudaphronesa Gaedike, 1972 (Ochromolopis), spec. n.